Detection of partial deletion and mosaicism using quantitative fluorescent polymerase chain reaction: Case reports and a review of the literature. Issue 8 (29th June 2022) - Xu, Chenxia; Peng, Jianming; Zhang, Yanfang; Liang, Shaoxia; Wang, Degang
Abstract: Background: Aneuploidy of chromosomes 13, 18, 21, X, and Y can be detected by the quantitative fluorescence polymerase chain reaction (QF‐PCR) performed with short tandem repeat (STR) markers. Although QF‐PCR is designed to detect whole chromosome trisomy, the partial deletion or mosaic of chromosomes may also be detected. Methods: Partial deletion or mosaic of chromosomes in three cases was detected by QF‐PCR. Karyotyping and chromosome microarray analysis(CMA) were performed. We further reviewed the clinical utility of QF‐PCR in detecting mosaicisms and deletions/duplications. Results: QF‐PCR demonstrated structurally abnormal 21, X, and Y chromosomes in primary amniotic cells. QF‐PCR results in these three cases showed abnormal peak height/peak area, which could not be interpreted according to the kit instructions. QF‐PCR results suggested that there were partial deletions or mosaicism, which were confirmed by karyotyping and CMA. Conclusion: In addition to detecting trisomies of whole chromosomes, QF‐PCR can also detect deletion and mosaicism of chromosomes 13, 18, 21, X, and Y, which could suggest the presence of copy number variants (CNVs). Additional testing with genetic technologies, such as karyotyping or microarrays, is recommended when an uninformative pattern is suspected. Abstract : QF‐PCR can detect deletion and mosaicism of chromosomes 13, 18, 21, X, and Y, which could suggest the presence of copy number variants (CNVs). The marker locations of short tandem repeat (STR) markers on chromosomes 3, 13, 18, 21, X, and Y. Here, we demonstrated that case 2 involved both mosaicism and a deletion. The orange arrow points to the AMXY (Xp22.3/Yp11.2) marker location with a ratio of 2.0 and the blue arrow points to the SRY (Yp11.2) location with a low peak, which indicates the loss of copy number in the Yp11.2 region. The green arrow points to TAF9b (3P24.2/Xq21.1) marker location with a peak area ratio of 2:1, indicating that is monosomy X. The black arrow points to DXYS267 (Xq21.31/Yp11.31) marker location with a peak height ratio of 0.66, which indicates that there is a deletion at the Yp11.2 region. The gray arrow points to DYS448 (Yq11.2) marker location with no signal peak height/area, indicating loss of Yq11.2 region. QF‐PCR can aid the discovery of deletion or mosaicism within STR loci, but further analysis by Next‐generation sequencing or microarray to confirm the diagnosis is necessary.